The Influence Of Perception Of Leadership Style And Climate Organization On Teacher Performance - Najmul Hidayat, Ayi; Ratnawulan, Teti; Hasim, Ismail; Makhmudah, Siti; Eko Purwanto, Muhammad (International Journal of Educational Research & Social Sciences, 2022)
The aims and objectives of this research are to answer three research questions: 1). to analyze the influence of leadership style on teacher performance; 2). Analyzing the influence of Organizational Climate on Teacher performance, and 3). analyze the influence of Leadership Style and organizational climate together on Teacher performance. The analytical method used in this research is descriptive analysis, simple linear regression, and multiple linear regression, using simultaneous significance experiments (F-test) and partial experiments (t-test), and the coefficient of certainty (R2), and using the SPSS type application program 21.0 version. The illustrations used in this research were obtained through the Non-Probability Sampling method of collecting images, namely sampling with 100 teachers. After testing the information, it is known that the Leadership Style (X1) has a positive effect on Teacher Ability (Y), with a Regression Coefficient of +0.481; significance level of 0.000 < 0.05; as a result (t-count) 5.284 > 1.985 (t-table), with a regression obtained Y = 90.005 + 0.481 X1 + e. After that, it was known that Organization Climate (X2) had a positive effect on Teacher Ability (Y), with a Regression Coefficient of +0.662; degrees of significance 0.000 < 0.05, as a result (t-count) 7.499 > 1.985 (t-table), with a regression obtained Y = 71.101 + 0.662 X1 + e. Finally, the Elastic Leadership Style (X1) and the Elastic Group Eve (X2) jointly have a positive effect on Teacher Ability (Y), with an F number of 31,614 and a chart F-number of 3,09. As a result, the F number is more significant than the F chart (31.614 > 3.09), with a significance level of 0.000 < 0.05.